2013
DOI: 10.1007/s00404-013-2784-1
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian epithelial tumors and reproductive factors: a systematic review

Abstract: The etiology and pathogenesis of ovarian cancer are still not fully understood. None of the so far proposed hypothesis on the development of OET can fully account for the epidemiologic and clinical findings in the context of reproductive factors and OET development. Further research approaches are warranted and need to put more weight on the clinical and genetical diversity of OET to yield a more detailed insight into their pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 219 publications
0
64
0
3
Order By: Relevance
“…Mucinous ovarian carcinoma is suggested to originate from non-ovarian cells and carries different risk factors than other ovarian cancer types [5]. Its risk has been reported not to be affected by oral contraceptives [16,17] but associations with HT use are inconsistent [7,17,18]. Progesterone receptor (PR) expression is lower in mucinous carcinomas than in other ovarian cancer subtypes [19] which may explain its resistance against the protective effect of oral contraceptives.…”
Section: Discussionmentioning
confidence: 97%
“…Mucinous ovarian carcinoma is suggested to originate from non-ovarian cells and carries different risk factors than other ovarian cancer types [5]. Its risk has been reported not to be affected by oral contraceptives [16,17] but associations with HT use are inconsistent [7,17,18]. Progesterone receptor (PR) expression is lower in mucinous carcinomas than in other ovarian cancer subtypes [19] which may explain its resistance against the protective effect of oral contraceptives.…”
Section: Discussionmentioning
confidence: 97%
“…The risk of GBC among women is 2-6 times that of men worldwide [46], suggesting the involvement of hormonal factors. During pregnancy, estrogen is highly elevated in serum [7,47]. The gallbladder contains both estrogen and progesterone receptors, and gallbladder tissue is sensitive to these hormones [48].…”
Section: Discussionmentioning
confidence: 99%
“…1,[4][5][6][7][8][9][10][11][12][13] For example, a collaborative reanalysis of 45 epidemiologic studies found the risk reduction afforded by OC use was evident for serous, endometrioid and clear cell, but not mucinous, tumors 13 and an analysis in the Ovarian Cancer Cohort Consortium (OCAC) found a positive association between body mass index (BMI) and risk of invasive endometrioid, mucinous and clear cell, but not high grade serous, tumors. 12 However, heterogeneous associations between BMI and EOC histologic subgroups have not been observed in all studies.…”
Section: What's New?mentioning
confidence: 99%